Desempenho de semeadora-adubadora em função do preparo de solo e espaçamento da cultura do milho - Chioderoli, Carlos Alessandro [UNESP]; Furlani, Carlos Eduardo Angeli [UNESP]; Silva, Rouverson Pereira Da [UNESP]; Gitti, Douglas De Castilho [UNESP]; Kaneko, Flávio Hiroshi [UNESP]; Roman, Rodrigo Alberto Alândia [UNESP] (Escola de Agronomia e Engenharia de Alimentos/UFG, 2010)
The performance of machines and agricultural implements are of fundamental importance, especially when subjected to different types of soil tillage, and have to adapt to these conditions, in order to promote good operational performance. The objective of this study was to analyze the operational performance of a Marchesan Supreme Cop grain drill, equipped with four rows, spaced 0.90 m, according to three types of tillage: conventional tillage (plowing and two harrowing series), reduced tillage (scarification with a roller), and no-tillage, in areas previously seeded with maize (Zea mays L.), at two spacing measures (0.90 m and 0.45 m). The results indicate that the demand for power, tensile stress, and motor rotation, in the sowing operation, were not influenced by tillage and maize crop. The tractor wheel slip showed different results, being lower in no-tillage and higher in conventional and reduced tillage.

O desempenho de máquinas e implementos agrícolas é de fundamental importância, principalmente quando estão sujeitos a diferentes tipos de preparo de solo, tendo que se adaptar a estas condições para promover uma boa capacidade operacional. Objetivou-se, com este trabalho, analisar o desempenho operacional de semeadora-adubadora Marchesan Cop Suprema, equipada com quatro fileiras, com espaçamento 0,90 m, em função de três tipos de preparo do solo: convencional (aração e duas gradagens), reduzido (escarificação com rolo destorroador) e semeadura direta, em área anteriormente semeada com milho (Zea mays L.), em dois espaçamentos (0,90 m e 0,45 m). Os resultados indicam que a exigência de potência, força de tração e rotação do motor, na operação de semeadura, não foram influenciadas pelo preparo do solo e cultivo do milho. A patinagem dos rodados do trator apresentou diferenças, sendo menor na semeadura direta e maior no preparo convencional e reduzido.
Performance of a grain drill in function of soil tillage and maize crop spacing
Keywords: Zea mays L; semeadura; capacidade operacional; patinagem; máquinas agrícolas; Zea mays L; sowing; operational capacity; wheel slip; agricultural machinery